Two-year clinical performance of an alkasite direct restorative material in class I and II cavities without using an adhesive resin: a prospective single-arm clinical trial - Öztürk Bozkurt, Funda; Toz Akalın, Tuğba; Özsoy Kaner, Alev; Kuşdemir, Mahmut; Özcan, Mutlu (My University, 2024)
Purpose: To evaluate the clinical performance of an alkasite material for Class I and Class II cavities. Methods: 50 subjects (30 females, 20 males; mean age: 28.7) referred to the Department of Restorative Dentistry, Medipol University, Dental School, Istanbul, Turkey, received 89 Class I and II restorations (Cention N) by two trained operators. All restorations were made in bulk application without an adhesive resin and without photo-polymerization. Results: 65 restorations were followed in 37 subjects at a 2-year recall. The mean observation period was 27.6 months. 24 restorations (13 subjects) were not followed up at 2-year recall and were considered as drop out. The restorations were made either due to primary caries (n= 73) or restoration replacement (n= 16). 89 restorations were placed of which 51 were in the maxilla and 38 in the mandible. In deep cavities, a cavity liner was applied (with n= 53; without n= 36). Hypersensitivity was observed in nine cases that disappeared at the latest after 1 month. No debonding, no fracture, and no endodontic complications were observed at 6-month and 1-year recalls whereas four partial retention losses and one pulpal complication occurred at the 2-year recall. The overall survival rate was 88.9% with a mean observation time of 27.6 months (Kaplan-Meier, Log Rank; Mantel-Cox) (95%CI=31.07-32.25).
Keywords: Adolescent; Dental Caries; Dental Restoration; Dentistry; Oral Surgery & Medicine